ANALYSIS OF THE USE OF THE ARIMA MODEL IN FORECASTING ECONOMIC INDICATORS - Turopova , Sohiba (INTERNATIONAL MULTIDISCIPLINARY SCIENCE CONFERENCE, 2026)
This article examines the analysis and forecasting of wholesale trade volume in the Surkhandarya region using time series methodsthe ARIMA model was applied to predict future values of the wholesale trade indicator. The stationarity of the time series was tested using the Augmented Dickey–Fuller test The findings of the study can be effectively used in regional economic planning and trade development strategies